Direct Transesterification of Microalgae Biomass and Biodiesel Refining with Vacuum Distillation - (:unkn) unknown (ELSEVIER SCIENCE BV, 2017)
The objective of this study was the use of vacuum distillation to increase fatty acid methyl ester (FAME) content and quality of microalgae biodiesel produced through direct transesterification. Microalgae biodiesel obtained from direct transesterification of microalgae (crude biodiesel) has a FAME content of 64.98 +/- 2.88%, viscosity of 17.7 +/- 0.17 (mm(2)/s), and a humidity level of 3.72%. As biodiesel s properties are related to FAME content, to increase FAME content and produce higher quality biodiesel two vacuum distillation experiments were conducted using different vacuum conditions. The best results were obtained in experiment 2 with two consecutive distillations, where FAME content increased from 64.98 +/- 2.88% in crude biodiesel to 85.50 +/- 2.60% in the D2.2 fraction, while viscosity decreased from 17.70 +/- 0.17 (mm(2)/s) in crude biodiesel to 3.76 +/- 0.01 (mm(2)/s) in the D2.2 fraction. Vacuum distillation, therefore, may represent an excellent alternative for the purification of microalgae-based biodiesel.